A prospective sonographic evaluation of peripheral intravenous catheter associated thrombophlebitis. Issue 5 (September 2022) - Mielke, Nicholas; Johnson, Steven; Karabon, Patrick; Bahl, Amit
Objective: Thrombophlebitis associated with peripheral intravenous catheters (PIVCs) is a poorly described complication in the literature. Given limited accuracy of current assessment tools and poor documentation in the medical record, the true incidence and relevance of this complication is misrepresented. We aimed to identify risk factors in the development of thrombophlebitis using an objective methodology coupling serial diagnostic ultrasound and clinical assessment. Methods: We conducted a single-site, prospective observational cohort study. Adult patients presenting to the emergency department that underwent traditionally placed PIVC insertion and were being hospitalized with an anticipated length of stay greater than 2 days were eligible participants. Using serial, daily ultrasound evaluations and clinical assessments via the phlebitis scale, we identified patients with asymptomatic and symptomatic thrombosis. The primary goal was to identify demographic, clinical, and IV related risk factors associated with thrombophlebitis. Univariate and multivariate analyses were employed to identify risk factors for thrombophlebitis. Results: A total of 62 PIVCs were included between July and August 2020. About 54 (87.10%) developed catheter-related thrombosis with 22 (40.74%) of the thrombosed catheters were characterized as symptomatic. Multivariate cox regression demonstrated that catheter diameter relative to vein diameter greater than one-third [AHR = 5.41 (1.91, 15.4) p = 0.0015] and angle of distal tip of catheter against vein wall ⩾5° [AHR = 4.39 (1.39, 13.8) p = 0.0116] were associated with increased likelihood of thrombophlebitis. Conclusions: Our study found that the increased proportion of catheter relative to vein size and steeper catheter tip angle increased the risk of thrombophlebitis. Catheter size relative to vein size is a modifiable factor that should be considered when inserting PIVCs. Additional larger prospective investigations using objective methodologies are needed to further characterize complications in PIVCs.